Efecto del decocto de cantua buxifolia en útero aislado de rattus norvegicus var. albinus - Salinas Díaz, Michael Collins (2014)
This study aimed to determine the effect of decoction of cantua buxifolia 20% isolated uterus rattus norvegicus var. albinus. Oxytocin, the pattern used was oxytocin: As the doses of decoction 1ml for both concentrations, 6 specimens were distributed into 2 groups were used. The analysis of the effect of 20% decoction on uterine contraction were increased amplitude at doses of 1 ml for the pattern and increase the frequency of contraction at the same dose as this variable is dose dependent, on induced contraction uterine muscle whose effects were obtained at this concentration (20%), as well as uterine activity was conditional on these two variables was also increased at this concentration. This observed effect is due to the presence of flavonoids and saponins